Suppose that the functions fand g are defined for all real numbers x as follows.f(x)=x+5g(x)=2x²Write the expressions for (g+f)(x) and (g–f)(x) and evaluate (g.f)(-3).
![Suppose that the functions fand g are defined for all real numbers x as followsfxx5gx2xWrite the expressions for gfx and gfx and evaluate gf3 class=](https://us-static.z-dn.net/files/d75/3bf793b83aa7b55ee84aae5e68e40953.png)
The expression (g+f)(x) is equal to g(x)+ f(x), (g-f)(x) is equal to g(x) f(x) and the expression (g*f)(-3) is equal to g(-3)*f(-3).
Then, we have
[tex](g+f)(x)=g(x)+f(x)=2x^2+x+5[/tex]Similarly,
[tex](g-f)(x)=g(x)f(x)=2x^2-(x+5)=2x^2-x-5[/tex]And finally,
[tex]\begin{gathered} (g\cdot f)(-3)=g(-3)\cdot f(-3)=2(-3)^2\cdot(-3+5) \\ (g\cdot f)(-3)=2(9)\cdot(2) \\ (g\cdot f)(-3)=36 \end{gathered}[/tex]In summary, the answers are:
[tex]\begin{gathered} (g+f)(x)=2x^2+x+5 \\ (g-f)(x)=2x^2-x-5 \\ (g\cdot f)(-3)=36 \end{gathered}[/tex]